The effect of omalizumab treatment on severe allergic asthma and allergic comorbidities: real-life experience from the Czech Anti-IgE Registry - Hutyrová, Beáta; Bystroň, Jaromír; Czech Anti-IgE Registry collaborators (Postepy dermatologii i alergologii, 2018)
INTRODUCTION: Omalizumab is indicated for the treatment of severe allergic asthma (SAA) and chronic spontaneous urticaria, although a number of studies have confirmed the effectiveness of this therapy also for other IgE-mediated diseases. AIM: To assess the impact of anti-IgE therapy on SAA and comorbid IgE-mediated allergic diseases in patients treated with omalizumab for SAA enrolled in the CAR (Czech Anti-IgE Registry). MATERIAL AND METHODS: Three hundred and ten patients with SAA treated with omalizumab were enrolled in the CAR. Two hundred and twenty-nine individuals were evaluated after 12 months of omalizumab treatment for asthma control test (ACT), examination of fractional exhaled nitric oxide (FENO), forced expiratory volume in 1 s (FEV1), the use of systemic corticosteroids, side effects of treatment and clinical effect of omalizumab on allergic comorbidities (allergic rhinitis, chronic urticaria, atopic dermatitis and food allergy). RESULTS: After 12 months of treatment with omalizumab, patients experienced a significant improvement of ACT and FEV1, reduction of FENO, use of systemic corticosteroids for asthma exacerbations and dose of maintenance oral corticosteroid therapy. The positive effect of treatment with omalizumab was observed in 82.2% of patients with allergic rhinitis, in 85.7% of patients with chronic urticaria, in 82.1% of patients with atopic dermatitis, and in 67.3% of patients with food allergy. CONCLUSIONS: In the CAR registry, patients with SAA treated with omalizumab showed a significant positive effect of anti-IgE therapy not only on the asthma control, but also on allergic comorbidities.
Keywords: allergic diseases; omalizumab; severe allergic asthma